Fungal Glucosylceramides: From Structural Components to Biologically Active Targets of New Antimicrobials - Nimrichter, Leonardo (Frontiers Research Foundation, 2011)
The first work reporting synthesis of glucosylceramide (cerebrin, GlcCer) by yeasts was published in 1930. During approximately 70 years members of this class of glycosphingolipids (GSL) were considered merely structural components of plasma membrane in fungi. However, in the last decade GlcCer was reported to be involved with fungal growth, differentiation, virulence, immunogenicity, and lipid raft architecture in at least two human pathogens. Fungal GlcCer are structurally distinct from their mammalian counterparts and enriched at the cell wall, which makes this molecule an effective target for antifungal activity of specific ligands (peptides and antibodies to GlcCer). Therefore, GSL are promising targets for new drugs to combat fungal diseases. This review discusses the most recent information on biosynthesis and role of GlcCer in fungal pathogens.